2010
DOI: 10.1111/j.1440-1681.2009.05319.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of cystic fibrosis transmembrane conductance regulator in mouse chondrocytes

Abstract: 1. Cystic fibrosis transmembrane conductance regulator (CFTR) is well known for its role in the cystic fibrosis (CF). Recent studies have shown that CF patients and CFTR-deficient mice exhibit a severe abnormal skeletal phenotype, indicating that CFTR may play a role in bone development and pathophysiological processes. However, it is not known whether CFTR has a direct or indirect effect on bone formation. The aim of the present study was to detect the expression and function of CFTR in mouse chondrocytes. 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…CF disease manifestations are typically related to loss of CFTR function at the plasma membrane in epithelial cells. However, differing mechanisms of CFTR function in nonepithelial cells have been proposed, including intracellular vesicle acidification and SR calcium homeostasis in skeletal muscle (41)(42)(43)(44). The lack of localized plasma membrane CFTR staining in ASM is similar to that in other nonepithelial cells and suggests an intracellular function of CFTR in ASM.…”
Section: /2mentioning
confidence: 87%
“…CF disease manifestations are typically related to loss of CFTR function at the plasma membrane in epithelial cells. However, differing mechanisms of CFTR function in nonepithelial cells have been proposed, including intracellular vesicle acidification and SR calcium homeostasis in skeletal muscle (41)(42)(43)(44). The lack of localized plasma membrane CFTR staining in ASM is similar to that in other nonepithelial cells and suggests an intracellular function of CFTR in ASM.…”
Section: /2mentioning
confidence: 87%
“…A second line, Cftr tm1Kth mice [10], express the mutated allele at a level of 25% relative to that of wild type mice expressing the wild type allele and this low level of expression in the intestine [10], but not other tissues including the lung, likely contributes to the lethal intestinal phenotype mice of this strain can develop. Although known to be expressed in bone [11,12] and in chondrocytes [13], the level of expression of Cftr in the bones of these ΔF508 Cftr mouse models has not been reported.…”
Section: Introductionmentioning
confidence: 90%
“…Animal models have shown that chondrocytes express functional CFTR [ 152 ], and cartilage abnormalities in tracheal ring structure have been reported in CF, both in humans and in animal models [ 153 , 154 ]. Both CFTR loss of function and local and systemic inflammation are hypothesised to be responsible for these changes, however, it is yet unclear whether cartilage abnormalities involve growth plate chondrocytes also, as these data are missing to date in the literature.…”
Section: Specific Changes In the Gh–igf Axis Igf System And Growmentioning
confidence: 99%